Kindergarten children's attachment security, inhibitory control, and the internalization of rules of conduct - Heikamp, Tobias; Trommsdorff, Gisela; Druey, Michel D.; Hübner, Ronald; von Suchodoletz, Antje (Frontiers in Psychology, 2013)
Starting from research on relations between attachment and the development of self-regulation, the present study aimed to investigate research questions on relations among inhibitory control, internalization of rules of conduct (i.e., behavior regulation, concern occasioned by others transgressions, confession, reparation after wrongdoing), and attachment security. Attachment security and internalization of rules of conduct of German kindergarten children (N = 82) were assessed by maternal reports. Children’s inhibitory control was measured with the Stop-task. Regression analyses revealed that inhibitory control was positively related to attachment security and to internalization of rules of conduct. Mediational analysis using a bootstrapping approach indicated an indirect effect of attachment security on internalization processes via inhibitory control. Implications for further research on the development of inhibitory control and internalization of rules of conduct are discussed.